Depressive symptoms in older adult couples: Associations with dyadic physical health, social engagement, and close friends - Miller, Lyndsey M.; Steele, Joel S.; Wu, Chao-Yi; Kaye, Jeffrey; Dodge, Hiroko H.; Gonzales, Mitzi M.; Lyons, Karen S. (Frontiers in Psychiatry, 2022)
Objective: The objective of this study was to examine associations between level of depressive symptoms in older adult spouse/partner couples and their physical health and social factors (social activity and number of close friends). Methods: Using data from 116 community-dwelling couples (age 76.2 ± 8.5), we simultaneously analyzed associations between depressive symptoms (Geriatric Depression Scale, range 0-11) and dyadic physical health, engagement in social activities, and connectedness with close friends. Results: Greater engagement in social activities was associated with fewer depressive symptoms in men, whereas more close friendships were associated with fewer depressive symptoms in women, controlling for partner effects, age, education, and cognitive function, with good model fit. Additionally, more disparate physical health within the couple (latent incongruence score) was associated with greater depressive symptoms in men. Discussion: Less social activity and fewer close friends were associated with depressive symptoms in older adult couples, but may be distinctly influential depending on gender and in the context of the older adult couple’s physical health.